Adopting zero interest financing model (ZIFM) in Islamic microfinance institutions: the case of Shariah people credit bank (BPRS), Indonesia - Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hasanudin (2014)
Microfinance has emerged as an important instrument to alleviate poverty in many countries including in developing countries. Despite being able to demonstrate successes in the activity, conventional microfinance is not without controversy. The findings from the existing studies revealed that conventional microfinance is less effective, fail to reach the poorest people and generally have a limited effect on income. In addition, conventional microfinance also has highly criticized for charging excessive interest rates and fees to the poor entrepreneur. In some Muslim countries, conventional microfinance has always been rejected, due to its noncompliance with the Islamic principles, particularly on the issue related to interest or riba. Islamic microfinance evolved and reckoned as an alternative to its counterpart. However, the outreach of Islamic microfinance is very limited where only there is very few Islamic microfinance institutions and Islamic banks involved in microfinance activity. Also, Islamic microfinance is having an issue of convergence of activity with the conventional practices. Thus, this paper aims to propose to adopt Zero Interest Financing Model (ZIFM) for Islamic microfinance institutions. This study focuses on the case of Indonesian Islamic microfinance institution namely Shariah People Credit Bank (BPRS) by observing their experience and some emerging issues. The proposed model is expected to address an emerging issue in Islamic microfinance institutions.